Question
upstudy study bank question image url

Use the Product Rule to find the derivative \( \frac{d}{d x}\left[\left(\frac{1}{3} x^{3}+\frac{2}{5} x^{5}\right)\left(\frac{2}{x}-4 x^{2}\right)\right] \)

Ask by Gonzalez Ortega. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative is \( \frac{dy}{dx} = \left(2 - \frac{2}{3}x\right) + \left(4 - \frac{4}{5}\right)x^{3} + \left(-\frac{8}{3} - 4\right)x^{4} + \left(-\frac{16}{5} - 8\right)x^{6} \).

Solution

To find the derivative of the expression \[ y = \left(\frac{1}{3} x^{3}+\frac{2}{5} x^{5}\right)\left(\frac{2}{x}-4 x^{2}\right) \] using the Product Rule, we will follow these steps: 1. **Identify the two functions**: - Let \( u = \frac{1}{3} x^{3} + \frac{2}{5} x^{5} \) - Let \( v = \frac{2}{x} - 4 x^{2} \) 2. **Differentiate each function**: - We need to find \( \frac{du}{dx} \) and \( \frac{dv}{dx} \). 3. **Apply the Product Rule**: - The Product Rule states that \( \frac{d}{dx}(uv) = u \frac{dv}{dx} + v \frac{du}{dx} \). Now, let's calculate \( \frac{du}{dx} \) and \( \frac{dv}{dx} \) step by step. ### Step 1: Differentiate \( u \) \[ u = \frac{1}{3} x^{3} + \frac{2}{5} x^{5} \] Using the power rule: \[ \frac{du}{dx} = \frac{1}{3} \cdot 3 x^{2} + \frac{2}{5} \cdot 5 x^{4} = x^{2} + 2 x^{4} \] ### Step 2: Differentiate \( v \) \[ v = \frac{2}{x} - 4 x^{2} \] This can be rewritten as \( v = 2x^{-1} - 4x^{2} \). Now, differentiating: \[ \frac{dv}{dx} = -2x^{-2} - 8x = -\frac{2}{x^{2}} - 8x \] ### Step 3: Apply the Product Rule Now we can apply the Product Rule: \[ \frac{dy}{dx} = u \frac{dv}{dx} + v \frac{du}{dx} \] Substituting \( u \), \( v \), \( \frac{du}{dx} \), and \( \frac{dv}{dx} \): \[ \frac{dy}{dx} = \left(\frac{1}{3} x^{3} + \frac{2}{5} x^{5}\right)\left(-\frac{2}{x^{2}} - 8x\right) + \left(\frac{2}{x} - 4x^{2}\right)\left(x^{2} + 2x^{4}\right) \] Now, we can simplify this expression to find the final derivative. Let's calculate this expression step by step. 1. Calculate \( u \frac{dv}{dx} \) 2. Calculate \( v \frac{du}{dx} \) 3. Combine the results. Let's perform these calculations. ### Step 1: Calculate \( u \frac{dv}{dx} \) \[ u \frac{dv}{dx} = \left(\frac{1}{3} x^{3} + \frac{2}{5} x^{5}\right)\left(-\frac{2}{x^{2}} - 8x\right) \] ### Step 2: Calculate \( v \frac{du}{dx} \) \[ v \frac{du}{dx} = \left(\frac{2}{x} - 4x^{2}\right)\left(x^{2} + 2x^{4}\right) \] Now, let's compute these two products. ### Step 1 Calculation \[ u \frac{dv}{dx} = \left(\frac{1}{3} x^{3} + \frac{2}{5} x^{5}\right)\left(-\frac{2}{x^{2}} - 8x\right) \] Expanding this: \[ = -\frac{2}{x^{2}} \cdot \frac{1}{3} x^{3} - 8x \cdot \frac{1}{3} x^{3} - \frac{2}{x^{2}} \cdot \frac{2}{5} x^{5} - 8x \cdot \frac{2}{5} x^{5} \] \[ = -\frac{2}{3} x + -\frac{8}{3} x^{4} - \frac{4}{5} x^{3} - \frac{16}{5} x^{6} \] ### Step 2 Calculation \[ v \frac{du}{dx} = \left(\frac{2}{x} - 4x^{2}\right)\left(x^{2} + 2x^{4}\right) \] Expanding this: \[ = \frac{2}{x} \cdot x^{2} + \frac{2}{x} \cdot 2x^{4} - 4x^{2} \cdot x^{2} - 4x^{2} \cdot 2x^{4} \] \[ = 2 + 4x^{3} - 4x^{4} - 8x^{6} \] ### Combine Results Now, we combine both results: \[ \frac{dy}{dx} = \left(-\frac{2}{3} x - \frac{8}{3} x^{4} - \frac{4}{5} x^{3} - \frac{16}{5} x^{6}\right) + \left(2 + 4x^{3} - 4x^{4} - 8x^{6}\right) \] Combining like terms will give us the final derivative. Let's simplify this expression. 1. Combine constant terms. 2. Combine \( x \) terms. 3. Combine \( x^{2} \) terms. 4. Combine \( x^{3} \) terms. 5. Combine \( x^{4} \) terms. 6. Combine \( x^{5} \) terms. 7. Combine \( x^{6} \) terms. After combining, we will have the final derivative. Let's perform the final simplification. ### Final Derivative Combining all terms, we get: \[ \frac{dy}{dx} = \left(2 - \frac{2}{3} x\right) + \left(4 - \frac{4}{5}\right)x^{3} + \left(-\frac{8}{3} - 4\right)x^{4} + \left(-\frac{16}{5} - 8\right)x^{6} \] This will yield the final expression for the derivative. If you need the

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of the given function using the Product Rule, we start by identifying our two functions. Let: \[ u = \frac{1}{3}x^{3} + \frac{2}{5}x^{5} \] \[ v = \frac{2}{x} - 4x^{2} \] The Product Rule states that: \[ \frac{d}{dx}[uv] = u'v + uv' \] Now, we need to calculate \(u'\) and \(v'\). 1. **Finding \(u'\)**: \[ u' = \frac{d}{dx}\left(\frac{1}{3}x^{3} + \frac{2}{5}x^{5}\right) = x^{2} + 2x^{4} \] 2. **Finding \(v'\)**: \[ v = \frac{2}{x} - 4x^{2} = 2x^{-1} - 4x^{2} \] \[ v' = \frac{d}{dx}\left(2x^{-1} - 4x^{2}\right) = -2x^{-2} - 8x = -\frac{2}{x^{2}} - 8x \] Now we can apply the Product Rule: \[ \frac{d}{dx}\left[\left(\frac{1}{3}x^{3} + \frac{2}{5}x^{5}\right)\left(\frac{2}{x} - 4x^{2}\right)\right] = u'v + uv' \] Substituting \(u\), \(u'\), \(v\), and \(v'\): \[ = \left(x^2 + 2x^4\right)\left(\frac{2}{x} - 4x^2\right) + \left(\frac{1}{3}x^3 + \frac{2}{5}x^5\right)\left(-\frac{2}{x^2} - 8x\right) \] To simplify: 1. **First Term**: \[ = (x^2 + 2x^4)\left(\frac{2}{x} - 4x^2\right) \] Distributing this, we have: \[ = x^2 \cdot \frac{2}{x} + x^2 \cdot (-4x^2) + 2x^4 \cdot \frac{2}{x} + 2x^4 \cdot (-4x^2) \] \[ = 2x + (-4x^4) + 4x^3 + (-8x^6) = 2x + 4x^3 - 4x^4 - 8x^6 \] 2. **Second Term**: \[ = \left(\frac{1}{3}x^3 + \frac{2}{5}x^5\right)\left(-\frac{2}{x^2} - 8x\right) \] Distributing this: \[ = \left(\frac{1}{3}x^3\right)\left(-\frac{2}{x^2}\right) + \left(\frac{1}{3}x^3\right)\left(-8x\right) + \left(\frac{2}{5}x^5\right)\left(-\frac{2}{x^2}\right) + \left(\frac{2}{5}x^5\right)(-8x) \] \[ = -\frac{2}{3}x + (-\frac{8}{3}x^4) - \frac{4}{5}x^3 - \frac{16}{5}x^6 \] Now, combine everything: Combining terms: - For \(x\): \(2x - \frac{2}{3}x = \frac{6}{3}x - \frac{2}{3}x = \frac{4}{3}x\) - For \(x^3\): \(4x^3 - \frac{4}{5}x^3 = \frac{20}{5}x^3 - \frac{4}{5}x^3 = \frac{16}{5}x^3\) - For \(x^4\): \(-4x^4 - \frac{8}{3}x^4\) can be

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy